PERTANIAN SEBAGAI KEARIFAN LOKAL PROPINSI JAWA TIMUR: PENDEKATAN VECTOR AUTOREGRESSION (VAR) - Ati Musaiyaroh; Panji Tirta N. P. (UPT Penerbitan Universitas Jember)
This article aims to determine the level of local knowledge relationship East Java province which is an agricultural area. The variables considered in this study, namely agricultural productivity as the dependent variable, while the area of crop area and population as independent variables. The method used is the vector autoregression (VAR). The results obtained show evidence that the artifacts long-term relationship between population and land area with the productivity of rice harvested from cointegration tests indicated that the existence of cointegration between variables. Test the optimum lag at lag 3 and the results showed that the variables that have contributed Most serious toward rice productivity is the number of residents of East Java.